Challenges in Preventing the Origin of Rheumatoid Arthritis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
General Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease, affecting 0.3 - 1% of the global population, with a higher incidence in women aged 20 - 40. Specific Background: It causes joint pain, stiffness, and potential systemic complications, including damage to the cardiovascular, respiratory, and nervous systems. Knowledge Gap: Despite advancements in pharmacological treatment, preventive strategies and rehabilitation efforts remain underexplored. Aims: This study aims to investigate preventive measures for RA and assess the effectiveness of rehabilitation programs. Results: The research emphasizes the role of lifestyle changes, early diagnosis, and rehabilitation in controlling disease progression. Novelty: The study fills a critical gap in RA management by integrating prevention and rehabilitation into clinical practice. Implications: The findings suggest that comprehensive management strategies, including education, rehabilitation, and lifestyle interventions, can improve patient outcomes and reduce disease-related disabilities.